2023
DOI: 10.1155/2023/8217910
|View full text |Cite
|
Sign up to set email alerts
|

Na4P2O7-Modified Biochar Derived from Sewage Sludge: Effective Cu(II)-Adsorption Removal from Aqueous Solution

Abstract: With the rapid development of industrialization, the amount of copper-containing wastewater is increasing, thereby posing a threat to the aquatic ecological environment and human health. Sludge biochar has received extensive concern in recent years due to its advantages of low cost and sustainability for the treatment of heavy-metal-containing wastewater. However, the heavy-metal-adsorption capacity of sludge biochar is limited. This study prepared a sodium pyrophosphate- (Na4P2O7-) modified municipal sludge-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 98 publications
(151 reference statements)
1
2
0
Order By: Relevance
“…The creation of composites was more efficient, varying depending on the type of additive and production method. Similar observations were reported by [ 73 ] who modified biochar with sodium pyrophosphate and also recorded a higher yield of such a composite compared to raw biochar. The highest efficiency was observed when creating the BC2 composite from biochar impregnated with FFHCO2.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The creation of composites was more efficient, varying depending on the type of additive and production method. Similar observations were reported by [ 73 ] who modified biochar with sodium pyrophosphate and also recorded a higher yield of such a composite compared to raw biochar. The highest efficiency was observed when creating the BC2 composite from biochar impregnated with FFHCO2.…”
Section: Resultssupporting
confidence: 90%
“…The higher ash content in the composites was caused by the additives used in the production of the composites. The results obtained by [ 73 ] indicate a higher ash content in biochar composites with the addition of copper compounds. BC1 and BC2 composites prepared with the addition of FFHCO2 were characterized by the highest ash content (78.36% and 49.76%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its sustainability and low-cost benefits for treating wastewater containing heavy metals, sludge biochar has recently attracted much attention [24]. It has been demonstrated that producing biochar from sewage sludge enables the safe processing of sewage sludge while also yielding an affordable and long-lasting sorbent [25]. The sorbents derived from sewage sludge typically possess a relatively large specific surface area (100-200 m 2 /g) and developed microporosity [22].…”
Section: Introductionmentioning
confidence: 99%